Analisis Peran Pustakawan untuk Meningkatkan Mutu Layanan Perpustakaan di Pondok Pesantren Al-Yusriyah Sei Meran Pangkalan Susu Kabupaten Langkat - Nadia Anggraini; Makmur Syukri; Fitri Hayati (Jurnal Budi Pekerti Agama Islam, 2024)
The research that has been done is entitled "Analysis of the Role of Librarianship to Improve Library Services at Pondok Pesantren Al-Yusriyah Sei Meran Pangkalan Susu Langkat Regency", which is motivated by the background that the Library is useful for improving the quality of education in schools, with the aim of supporting the general education curriculum and developing interest in reading. To achieve the goal of quality service, the library is required to meet the needs of its librarians. Not only the fulfillment of information sources, but it is also necessary to pay attention to physical facilities, service quality, and technology that can help the service process so as to achieve user satisfaction. A descriptive qualitative research method was used to conduct this research, providing a more thorough explanation of the research topic. Three data collection methods were used: documentation, interviews, and observation. Interviews in the form of guidelines with several questions were used as study aids. Data reduction, data presentation, and drawing conclusions were used in data analysis techniques, triangulation, including triangulation of sources and theories. The results of the study revealed that (1) The role of librarians at AlYusriyah Islamic Boarding School in improving the quality of library services is very good, it's just that it is necessary to compile a more detailed budget plan and submit it to the school or government, (2) Develop and implement appropriate strategies to attract students and increase visits to the library, (3) and face various significant obstacles, such as limited funds, lack of funds has an impact on inadequate facilities and infrastructure, such as narrow library space and lack of reading facilities. Based on the research findings above, improving the quality of library services is worth applying and implementing as a solution to improve the quality of a more disciplined library to create a quality educational environment.